Ambivalent texts, the borderline, and the sense of nonsense in Lewis Carroll’s “Jabberwocky” - Templeton, Michael (International Journal of English Studies, 2019)
Taking Carroll’s “Jabberwocky” as emblematic of a text historically enjoyed by both children and adults, this article seeks to place the text in the area of what Kristeva defines as the borderline of language and subjectivity in order to theorize a site by which ambivalent texts emerge as such. The fact that children’s literature remains largely trapped in the literary didactic split in which these texts are understood as either learning materials or primers toward literacy, the article situates Carroll’s text in theories of language, subjectivity, and clinical discourse toward are more complex reading of a children’s text.